Managerial Pay Raise and Promotion Decisions for Workers with I-deals. Issue 1 (February 2023) - Tomprou, Maria; Simosi, Maria; Rousseau, Denise M.
Managers use idiosyncratic deals (i-deals) to motivate and retain employees. Yet we know little about the subsequent effects i-deals have on decisions about pay raises and promotions. Two studies investigate how managers make pay raise and promotion decisions for workers with i-deals. Using a policy-capturing design, managers ( N = 116) made pay raise and promotion allocations for workers presented as good performers, based on information provided regarding whether and what type of i-deal workers had and the extent to which they helped peers. Developmental i-deal recipients tend to be recommended for both pay raises and promotions, while such recommendations are less likely for employees with flextime i-deals (for promotions) or reduced workload i-deals (for promotions and pay raises). In addition, workers with i-deals who help their peers are viewed more favorably in both decisions. The second study surveyed managers ( N = 174) regarding their actual subordinates ( N = 806), both controlled for the manager's rating of subordinate performance. It supports the positive effect of developmental i-deals on pay and promotion decisions, but not the negative effects of flextime and reduced workload i-deals. Helping effects depend on the i-deal: Managers report that unhelpful recipients of developmental i-deals are less likely to be promoted than those with such i-deals who help their peers; unhelpful recipients of reduced workload i-deals are less likely to get pay raises than those with such deals who help. We discuss the implications of our findings for future research and career management.